Identification and screening for antimicrobial activities in lactic acid bacteria from yogurt - Mohd Jaini, Mohammad Fahrulazri (2015)
Objectives of this study were to screening for the antimicrobial activity of lactic acid bacteria, to identify the species of the lactic acid bacteria, and to determine its minimum inhibitory concentration. Four isolates of unknown bacteria were obtained from Mycology Laboratory, Department of Microbiology, Faculty of Biotechnology and Biomolecular Science, UPM. All of the isolates were cultured from four different sources. Among the four isolate, three were observed as Saccharomyces cerevisae or yeast due to its gram stain morphology which is has budding like structure. On the other hand, Y1 show rod shape morphology and gram positive due to its purple colour. Screenings of antimicrobial activity of Y1 show that the growth of Listeria monocytogenes and Escherichia coli were inhibited by the bacteria. Set of biochemical test was done for Y1 only and Y1 was identified as Lactobacillus sp.. Critical dilution method determined that the arbitrary unit of the bacteria supernatant inhibit both Listeria monocytogenes and Escherichia coli were at 20 AU/mL. With regard to the antibacterial effect of the lactobacilli strains in this study, they may help in the treatment of Listeria monocytogenes and Escherichia coli associated diseases and can be applied as a biological preservative in the food industry.